A Note on Some Applications of Boyadzhiev’s Formula - Thapa, Gyan Bahadur; López-Bonilla, J.; López-Vázquez, R. (Journal of the Institute of Engineering, 2018)
In this paper, we employ an expression of Boyadzhiev to give elementary proofs of the identities for harmonic numbers obtained by Paule-Schneider via the Mathematica package Sigma. Journal of the Institute of Engineering, 2017, 13(1): 175-177